+0  
 
+2
130
1
avatar+195 

\(\displaystyle\lim_{x\to0}(\frac{\sin{x}}{x})^\frac{1}{1-\cos{x}}\)

Rollingblade  Jun 6, 2018

Best Answer 

 #1
avatar+945 
+2

\(\text{Compute}:\displaystyle\lim_{x\to0}(\frac{\sin{x}}{x})^\frac{1}{1-\cos{x}}\)

 

We can approximate \(\sin{x} \text{ and } \cos{x}\) by their Taylor series.

 

After apply substitutions:

 

\(\displaystyle\lim_{x\to0}(\frac{\sin{x}}{x})^\frac{1}{1-\cos{x}}=\lim_{x\to0}(1-\frac{x^2}{6})^\frac{2}{x^2}=\lim_{x\to0}(1+\frac{x^2}{6})^{-\frac{2}{x^2}}\)

 

\(=\displaystyle\lim_{x\to\infty}(1+\frac{1}{6x^2})^{-2x^2}=\lim_{x\to\infty}(1+\frac{1}{x})^{-x/3}=\boxed{e^{-1/3}}\)

 

This is because \(e=\displaystyle\lim_{x\to\infty}(1+\frac1x)^x\)

 

I hope this helped,

 

Gavin

GYanggg  Jun 6, 2018
 #1
avatar+945 
+2
Best Answer

\(\text{Compute}:\displaystyle\lim_{x\to0}(\frac{\sin{x}}{x})^\frac{1}{1-\cos{x}}\)

 

We can approximate \(\sin{x} \text{ and } \cos{x}\) by their Taylor series.

 

After apply substitutions:

 

\(\displaystyle\lim_{x\to0}(\frac{\sin{x}}{x})^\frac{1}{1-\cos{x}}=\lim_{x\to0}(1-\frac{x^2}{6})^\frac{2}{x^2}=\lim_{x\to0}(1+\frac{x^2}{6})^{-\frac{2}{x^2}}\)

 

\(=\displaystyle\lim_{x\to\infty}(1+\frac{1}{6x^2})^{-2x^2}=\lim_{x\to\infty}(1+\frac{1}{x})^{-x/3}=\boxed{e^{-1/3}}\)

 

This is because \(e=\displaystyle\lim_{x\to\infty}(1+\frac1x)^x\)

 

I hope this helped,

 

Gavin

GYanggg  Jun 6, 2018

15 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.